The Organizational Innovativeness of Public Listed Housing Developers in Malaysia - Yusof, Nor’Aini; Abu-Jarad, Ismael Younis (World Academy of Science Engineering and Technology, 2011)
This paper investigated the organizational innovativeness of public listed housing developers in Malaysia. We conceptualized organizational innovativeness as a multi-dimensional construct consisting of 5 dimensions: market innovativeness, product innovativeness, process innovativeness, behavior innovativeness and strategic innovativeness. We carried out questionnaire survey with all accessible public listed developers in Malaysia and received a 56 percent response. We found that the innovativeness of public listed housing developers is low. The paper ends by providing some explanations for the results.